2022
DOI: 10.1002/poh2.35
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in cirrhosis patients with upper gastrointestinal bleeding: An updated systematic review and meta‐analysis

Abstract: ObjectiveEmerging evidence suggest that antibiotic prophylaxis may be omitted in early cirrhosis patients with upper gastrointestinal bleeding (UGIB), which question the benefits of antibiotic prophylaxis on rebleeding, mortality related to ongoing bleeding, and the need for salvage therapy. As the management of UGIB has improved over time since the last review a decade ago, we performed an updated meta‐analysis to review the benefits of antibiotic prophylaxis in cirrhosis patients with UGIB.MethodSix electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…An emerging concept proposed is identifying risk factors and possible avoidance of antibiotics in patients with well-preserved liver functions presenting with VH, however, prospective validation is needed (27,28). Although the model for end-stage liver disease (MELD) is reasonable in predicting outcomes of patients with VH, a recent study reported MELD-Lactate to be superior in predicting mortality after VH (29,30).…”
Section: Newer Perspectivesmentioning
confidence: 99%
“…An emerging concept proposed is identifying risk factors and possible avoidance of antibiotics in patients with well-preserved liver functions presenting with VH, however, prospective validation is needed (27,28). Although the model for end-stage liver disease (MELD) is reasonable in predicting outcomes of patients with VH, a recent study reported MELD-Lactate to be superior in predicting mortality after VH (29,30).…”
Section: Newer Perspectivesmentioning
confidence: 99%
“…3,4 The cover image for the third issue described the benefit of antibiotic prophylaxis for patients with early cirrhosis and upper gastrointestinal bleeding. 5 This updated meta-analysis on 18 studies and 3180 cirrhotic patients found that antibiotic prophylaxis reduced mortality at 6 weeks, risk of infection, and infectionrelated mortality. 5 The idea of this study reminded the illustrators of Butterflies in Love with Flowers, a legendary song poetry in Chinese culture.…”
mentioning
confidence: 99%
“…5 This updated meta-analysis on 18 studies and 3180 cirrhotic patients found that antibiotic prophylaxis reduced mortality at 6 weeks, risk of infection, and infectionrelated mortality. 5 The idea of this study reminded the illustrators of Butterflies in Love with Flowers, a legendary song poetry in Chinese culture. The painting metaphorically represented the stomach and bleeding as a vase and red flowers while prophylactic antibiotic treatment as a butterfly.…”
mentioning
confidence: 99%